Population dynamics of the seabob shrimp Xiphopenaeus kroyeri (Dendrobranchiata, Penaeidae) in south-eastern Brazil - Heckler, G.; Simões, S. [UNESP]; Santos, APF [UNESP]; Fransozo, A. [UNESP]; Costa, R. [UNESP] (National Inquiry Services Center (NISC), 2013)
The population dynamics, including the sex ratio, reproductive period, individual growth and longevity, and population structure of the shrimp Xiphopenaeus kroyeri, are described. The shrimps were collected monthly from July 2005 to June 2007 at four sites in Ubatuba Bay, Brazil. The salinity, temperature, depth, organic matter content and sediment grain size were measured at each site. Specimens were quantified and sexed, their carapace length measured and their gonads were classified according to the stage of maturation. A von Bertalanffy model was used to estimate the individual growth, and longevity was calculated using its inverted formula. In total, 6 470 individuals were examined and the number of males and females differed significantly in favour of females. During some periods, the segregation could be related to the reproductive period. Reproductive females were captured throughout the sampled period, and there were biannual peaks that were followed by peaks of juveniles. Carapace growth was less for males than for females, which is likely related to oocyte production and the higher fecundity of the females. The higher probability of female capture can be related to their longer foraging to sustain the enhanced food requirement during the ovarian maturation period. © 2013 Copyright NISC (Pty) Ltd.
Keywords: closed season; growth; longevity; recruitment; reproductive period; sex ratio; fecundity; grain size; maturation; organic matter; population dynamics; population structure; recruitment (population dynamics); salinity; sediment; shrimp culture; temperature; Brazil; Sao Paulo [Brazil]; Ubatuba Bay